Optimization of polyphenols encapsulation from Orthosiphon Stamineus - Muhammad Mu’izzuddin, Abd Malek (2015)
Orthosiphon stamineus, O. stamineus, (vernacular name: ‘misai kucing’), is a traditional herb that can be found grows in Southeast Asia. O. stamineus is a herbal shrub with well-developed creeping rootstock. The leaves are simple, green, and arranged in opposite pairs. O. stamineus is used as traditional remedy for joint inflammation, gout, diabetes, oedema, eruptive fever, jaundice, arthritis, rheumatism diuresis, hepatitis, urinarylithiasis, influenza hypertension, and kidney stones. The phenolic compounds content in O. stamineus as antioxidant source is proven there. There are some research done about microencapsulation of polyphenols from O. stamineus, however, there is not much optimization protocol has been established for phenolic extraction and microencapsulation from O. staminues. Hence, the aim of this study is to optimize the polyphenol extraction from O. stamineus by studying the effects of temperature on the recovery of phenolic compounds in spray dryer, and total solid percentage and the maltodextrin/whey protein mix in microencapsulation. UPLC is used to analyze moisture, total solid and total flavonoid content. The optimization on parameters such as temperature, total solid content and ratio of microencapsulation material shall be done using Response Surface Modelling (RSM) and some other software like Design-Expert and Microsoft Excel. This research project is expected to deliver the least phenolic content degradation based on parameters involved.